Use of chitosan impregnated modified bentonite as an adsorbent for remediation of oil spill from aqueous solution - Waheed Thany, Zena; Mousa Ridha, Ali (International Journal of Engineering and Technology, 2018)
The focus of this work was to study the removal of oil spill from aqueous solution by adsorption onto different adsorbents such as raw bentonite (RB), modified bentonite (MB), chitosan-modified Bentonite (CS-MB10) and Chitosan-modified Bentonite (CS-MB30). The CS-MB10 and CS-MB30 were prepared by loading biopolymer Chitosan onto modified bentonite with different amounts of chitosan as 10 wt.% and 30 wt. % respectively. The modified bentonite was made by exchanging Cetyltrimethylammonium bromide (CTAB) with calcium ions in the Iraqi bentonite structure. All adsorbents were characterized by FTIR, surface area and pore volume. The maximum adsorption efficiency of oil at 1.4g was found to be 72.46% for RB, 89.09% for MB, and at 1.2g were found to be 90.81 % for CS-MB10 and 95.85 % for CS-MB30. Best contact time and pH were selected at 2 h and pH 6 with the maximum adsorption efficiency of oil onto each of RB, MB, CS-MB10 and CS-MB30. The Temkin isotherm gave a better fit to the experimental data than Langmuir and Freundlich adsorption isotherm for oil removal onto CS-MB10 and RB and the Langmuir isotherm gave a better fit to the experimental data than Temkin and Freundlich adsorption isotherm for oil onto CS-MB30 and MB.